Association of tricuspid regurgitation with clinical and echocardiographic outcomes after percutaneous mitral valve repair with the MitraClip System: 30-day and 12-month follow-up from the GRASP Registry. (17th June 2014) - Ohno, Yohei; Attizzani, Guilherme F.; Capodanno, Davide; Cannata, Stefano; Dipasqua, Fabio; Immé, Sebastiano; Barbanti, Marco; Ministeri, Margherita; Caggegi, Anna; Pistritto, Anna M.; Chiarandà, Marta; Ronsivalle, Giuseppe; et al.
Abstract: Aim: The aim of this study was to evaluate the association of baseline tricuspid regurgitation (TR) on the outcomes after percutaneous mitral valve repair (PMVR) with the MitraClip system. Methods and results: Data from 146 consecutive patients with functional mitral regurgitation (MR) were obtained. Two different groups, dichotomized according to the degree of pre-procedural TR (moderate/severe, n = 47 and none/mild, n = 99), had their clinical and echocardiographic outcomes through 12-month compared. At 30-day, the primary safety endpoint was significantly higher in moderate/severe TR compared with none/mild TR (10.6 vs. 2.0%, P = 0.035). Marked reduction in MR grades observed post-procedure were maintained through 12 months. Although NYHA functional class significantly improved in both groups compared with baseline, it was impaired in moderate/severe TR compared with the none/mild TR group (NYHA > II at 30 day: 33.3 vs. 9.2%, P < 0.001; at 1 year: 38.5 vs. 12.3%, respectively, P = 0.006). Left ventricle reverse remodelling and ejection fraction improvement were revealed in both groups. The primary efficacy endpoint at 12-month determined by freedom from death, surgery for mitral valve dysfunction, or grade ≥3+ MR was comparable between groups, but combined death and re-hospitalization for heart failure rates were higher in the moderate/severe TR group. Multivariable Cox regression analysis demonstrated that baseline moderate/severe TR and chronic kidney disease were independent predictors of this combined endpoint. Conclusions: Although PMVR with MitraClip led to improvement in MR, TR, and NYHA functional class in patients with baseline moderate/severe TR, the primary safety endpoint at 30-day was impaired, while moderate/severe TR independently predicted death and re-hospitalization for heart failure at 12-month.